Передумови впливу міграції на правосвідомість і правову поведінку українських трудових мігрантів - Садикова, Я. М.; Sadykova, Y. M.; ORCID: http://orcid.org/0000-0002-2841-8324; ResearcherID: D-1543-2018; Бондарєв, В. В.; Bondariev, V. V. (Вісник Запорізького національного університету. Юридичні науки. - 2020. - № 1. - С. 15-20, 2020)
Міграція та висока мобільність є характеристиками сучасного світу. Міграція (будь-якого типу) безпосередньо впливає на правосвідомість учасників міграційних процесів. Натепер немає єдиного стандарту в області інтеграції мігрантів у країнах Європейського Союзу, але це питання є одним з актуальних у сучасному світі. Це спроба оцінки фактичного впливу трудової імміграції в міждисциплінарному підході з урахуванням об’єкта впливу – правової культури й правосвідомості. Міграція є свого роду соціальним «каталізатором». Трудові мігранти з України мають низький рівень правової культури й, набуваючи негативний соціальний і правовий досвід, дають нове джерело розвитку нелегального ринку праці й тіньової економіки, поширення корупційних відносин і нелегальних схем. Все це негативно впливає на розвиток суспільства як приймальної країни, так і країни-донора трудових мігрантів. Відзначено, що інформаційно-психологічні методи можуть істотно впливати на рівень правової культури осіб, залучених до міграційних процесів.

Migration and high mobility are characteristics of the modern world. Migration (of any type) directly affects the legal consciousness of migration processes participants. Today there is no unified standard in the field of integration of migrants in the countries of the European Union, but this issue is one of the most important in the modern world. It is the attempt of assessing the actual impact of labor immigration in an interdisciplinary approach, taking into account the object of influence – legal culture and legal consciousness. Thus, immigrants who aim at a long stay in the country, are already partially ready to adopt new traditions and living conditions for them. As a rule, in the process of preparing documents for moving to another country, a person learns a foreign language and language adaptation is easier. At the same time, legal and illegal labor migrants face with low-skilled work with excessive physical exertion, deliberate non-compliance with the regulated requirements for working conditions, the inability to assert their own rights, and the absence of an appeal mechanism for violations, which probably only deepens the extremely low level of legal culture of labor migrants. Therefore, this problem is very relevant in terms of finding ways to improve the legal culture of labor migrants – citizens of Ukraine working abroad, in order to prevent the loss of their socio-demographic, labor potential. Migration is a kind of social “catalyst”. Migrant workers from Ukraine have a low level of legal culture, and, gaining negative social and legal experience, give a new round to the development of the illegal labor market and the shadow economy, the spread of corruption relations and illegal schemes. All this negatively affects the development of society, both of the host country and of the donor country of labor migrants. Young people and people with higher education are important objects of regulation of migration processes that are more sensitive to the situation in the region and have high negative migration expectations. It is noted that information-psychological methods can significantly affect the level of legal culture of persons involved in migration processes.

Миграция и высокая мобильность являются характеристиками современного мира. Миграция (любого типа) непосредственно влияет на правосознание участников миграционных процессов. На данный момент нет единого стандарта в области интеграции мигрантов в странах Европейского Союза, но этот вопрос является одним из актуальных в современном мире. Это попытка оценки фактического влияния трудовой иммиграции в междисциплинарном подходе с учетом объекта воздействия - правовой культуры и правосознания. Миграция является своего рода социальным «катализатором». Трудовые мигранты из Украины имеют низкий уровень правовой культуры и, приобретая негативный социальный и правовой опыт, дают новый источник развития нелегального рынка труда и теневой экономики, распространение коррупционных отношений и нелегальных схем. Все это негативно влияет на развитие общества как приемной страны, так и страны-донора трудовых мигрантов. Отмечено, что информационно-психологические методы могут существенно влиять на уровень правовой культуры лиц, вовлеченных в миграционные процессы.
The prerequisites for the impact of migration on the legal consciousness and legal behavior of Ukrainian labor migrants
Садикова, Я. М. Передумови впливу міграції на правосвідомість і правову поведінку українських трудових мігрантів / Садикова Я. М., Бондарєв В. В. // Вісник Запорізького національного університету. Юридичні науки. - 2020. - № 1. - С. 15-20. - DOI: https://doi.org/10.26661/2616-9444-2020-1-02.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; умови міграції; трудовий мігрант; правосвідомість; правова поведінка; сучасні тенденції; українська міграція; передумови міграції; міграція; миграция; трудовой мигрант; правосознание; правовое поведение; украинская миграция; conditions of migration; prerequisites of migration; labor migrant; legal consciousness; legal behavior; modern trends of Ukrainian migration